Psychiatrists in Combat : Mental Health Clinicians' Experiences in the War Zone - Ritchie, Elspeth Cameron; Warner, Christopher H.; McLay, Robert N. (Springer International Publishing : Imprint: Springer, 2017)
This book tells the professional and personal experiences of American military psychiatrists and their fellow mental health providers in the longest conflict in American history. These men and women treat service members for the psychological consequences from their experiences in battle, including killing enemy combatants; seeing wounded and killed civilian casualties; losing their friends in combat; factoring in personal mental health needs,; and potentially dealing with their own physical injuries from being shot or blown up. The volume consists of 20 short first-person case studies from mental health providers who have been risking their lives while treating patients in the battlefield since 9/11. Written by experts who have experienced these challenges directly, this text offers both clinical and personal accounts that are not found elsewhere. Topics include tips on providing psychotherapy in battle, evaluating and treating detainees in war prisons such as Abu Ghraib and Guantanamo Bay, and the unique challenges of prescribing medication to patients who are also comrades in war. Psychiatrists in Combat; Mental Health Clinicians in the War Zone is uniquely positioned to be a valuable resource for psychiatrists interested in trauma and veterans, psychologists, social workers, occupational therapists, military health personnel, and mental health professionals interested in military psychiatry. .